Brazilian network of COVID-19 during pregnancy (REBRACO: A multicentre study protocol) - Costa, Maria Laura; Souza, Renato T; Pacagnella, Rodolfo C; Bento, Silvana F; Ribeiro-Do-Valle, Carolina C; Luz, Adriana G; Lajos, Giuliane J; Mazon, Silvia B; Bahamondes, Luis; Surita, Fernanda G.; Nobrega, Guilherme M.; Griggio, Thayna B; et al. (BMJ, 2021)
Introduction The aim of this study was to evaluate the clinical, epidemiological and laboratory aspects of SARS-CoV-2 infection during pregnancy and postpartum in 16 maternity hospitals. Methods and analysis A prospective multicentre study, with five axes. First, the prevalence of SARS-CoV-2 infection among women admitted for childbirth will be described in a cross-sectional study. Second, maternal and perinatal outcomes will be assessed in a prospective cohort study including pregnant or postpartum women with suspected COVID-19. Third, a cohort of positive COVID-19 cases with sampling of a variety of biological material. Histopathological and viral analysis of biological maternal and neonatal samples will be performed, and the assessment of nutritional variables to evaluate the association between vitamin D and severity of infection. Fourth, a monitoring and evaluation committee to collect relevant healthcare information and plan actions in centres facing the pandemic. Furthermore, qualitative studies will be performed to study pregnant women, their families and health professionals. Fifth, an ecological study will monitor the number of live births, stillbirths and other outcomes to explore any trend among the periods before, during and after the pandemic. Data will systematically be collected in an electronic platform following standardised operational procedures. For quantitative study components, an appropriate statistical approach will be used for each analysis. For qualitative data, in-depth interviews recorded in audio will be transcribed, checking the text obtained with the recording. Subsequently, thematic analysis with the aid of the NVivo programme will be performed. Ethics and dissemination Ethical approval was obtained (letters of approval numbers 4.047.168, 4.179.679 and 4.083.988). All women will be fully informed to sign the consent form before enrolment in the study. Findings will be disseminated through peer-reviewed journals and scientific conferences.
Keywords: COVID-19; infection control; maternal medicine; prenatal diagnosis; qualitative research